2023
DOI: 10.12659/aot.940502
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Membranoproliferative Glomerulonephritis After Kidney Transplantation: Risk Factors and Impact on Graft Survival

Abstract: Background Membranoproliferative glomerulonephritis (MPGN) is an uncommon cause of end-stage renal disease (ESRD). Recurrence rates after transplantation range from 11.8% to 18.9% after 5 and 15 years, respectively. This study aimed to assess the risk factors of MPGN recurrence after kidney transplantation and its impact on graft survival. Material/Methods This was a single-center retrospective cohort, including renal transplant recipients older than 18 years, with a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
1
1
Order By: Relevance
“…In line with these observations, another study showed that in patients with MPGN as a primary disease, the presence of nephrotic syndrome and complement consumption in a native kidney predicts a more severe disease. In this analysis, the impact of MPGN was lower compared to the literature (between 11.8% and 18.9%), probably due to the maintenance therapy with corticosteroids after KTs [21].…”
Section: Factor B [Fb] Factor H [Fh] Factor I [Fi]contrasting
confidence: 72%
“…In line with these observations, another study showed that in patients with MPGN as a primary disease, the presence of nephrotic syndrome and complement consumption in a native kidney predicts a more severe disease. In this analysis, the impact of MPGN was lower compared to the literature (between 11.8% and 18.9%), probably due to the maintenance therapy with corticosteroids after KTs [21].…”
Section: Factor B [Fb] Factor H [Fh] Factor I [Fi]contrasting
confidence: 72%
“… 38 , 39 A retrospective study by our group, including recipients of kidney transplantation with CKD secondary to MPGN, showed a recurrence rate of 25%, most recipients of kidneys from living donors, like that observed in other studies. 40 The MPGN recurrence rate is higher among patients with complement-mediated MPGN than immune complex-mediated MPGN. 41 The recurrence rate of DDD is high, reaching 100% in some studies, with a 5-year rate of graft failure of 50%.…”
Section: Immune Complex and Complement-mediated Membranoproliferative...mentioning
confidence: 99%